The effect of age, gender, and body mass index on the pharmacokinetics and pharmacodynamics of vildagliptin in healthy volunteers - He, Yan-Ling (Blackwell Science Inc, 2008)
AIMS: To evaluate the effect of age, gender, and body mass index (BMI) on the pharmacokinetics and pharmacodynamics of vildagliptin. METHODS: Forty healthy subjects received a single oral dose of 100 mg vildagliptin to assess the effects of age, gender, and BMI on the pharmacokinetics and pharmacodynamics, reflected by the time course of inhibition of DPP-4 activity, of vildagliptin. RESULTS: Peak concentration and exposure (AUC((0–∞))) of vildagliptin were 17% (90% CI 2, 35%) and 31% (90% CI 18, 45%) higher in elderly vs. young subjects. Renal clearance was reduced by 32% (90% CI 17, 45%) in elderly subjects. The pharmacokinetics of vildagliptin were not significantly influenced by gender or BMI. Inhibition of DPP-4 activity was similar regardless of age, gender, or BMI. CONCLUSIONS: The pharmacokinetics of a single oral 100 mg dose of vildagliptin were not affected by gender and BMI. Exposure to vildagliptin was higher in elderly patients, but this was not associated with any difference in the effect of DPP-4 inhibition. Based on these results, no vildagliptin dose adjustment is necessary for age, gender, or BMI.